Kilka uwag o genezie islamu w Afryce Północnej - Piwko, Aldona Maria (Annales Missiologici Posnanienses, 2012)
The first country conquered by Muslims in North Africa was Egypt. Arabic rules started there already in 642, only ten years after Muhammad’s death. North Africa underwent a strong processes of islamization as a result of the Arabic expansion in the Middle Ages. Arabs started to refer to these territories of North Africa as „Maghreb” – Arabic word for “West”. The expansion of the Islam caused irreversible changes of African continent in all social, cultural and political dimensions.